Academic Literacies in Higher Education in Parana: Opportunities and Shortcomings - Sanches, Bruno Silva; Cristovao, Vera Lucia Lopes [UNESP] (Assoc Nac Pos-graduacao Pesquisa Letras & Linguistica, 2021)
Studies in academic literacies emerge from the necessity to expand and/or investigate the opportunities for students' engagement and agency in academia. The university is an educational environment, which requires students to deal with a diverse range of social situations involving genres such as research articles, reading projects, oral presentations, among others, and their social roles implied. Based on the model of academic literacies by Lea and Street (1998), we analyse the prospects of actions a public University of Parana State has (or has not) provided to facilitate the development and inclusion of its students in the production and understanding of academic genres, focusing on the opportunities for engaging with texts in Portuguese (mother tongue), English, Spanish, and/or French. In order to gather data, an online questionnaire was used and a focus group run with 4th-year students of an English Language Teacher Education course. The results show considerable shortcomings and needs for improvement especially concerning academic literacy development in additional languages and the necessity for more opportunities to supply demands shown in this study from the data analysed.
Keywords: Academic literacies; Textual genre; English language; Academic writing; Additional languages